Mecânica do dano concentrado aplicada a pórticos planos de concreto armado para modos de falha por esforços de flexão e cortante com fator de correção da variável de dano - Pereira Neto, Renério (2024)
The numerical idealization of the mechanical behavior of civil engineering structures has gained visibility in recent decades. The use of computational tools to adequately simulate real engineering problems ensures continuous advancements in the development of new studies, codes, and standards, as well as significantly contributing to the prevention of structural failures and incidents in the relevant field. Focusing on reinforced concrete structures, concrete cracking and steel yielding are nonlinear phenomena that complicate the construction of a consistent numerical model. Numerical models capable of simulating experimentally observed nonlinear phenomena are grounded in more advanced theories, namely plasticity theory, fracture mechanics, and continuum damage mechanics. Despite the significant advances made by these theories, their application in practical civil engineering problems has limited applications due to the high computational cost involved, the need to consider initial cracks, among other factors. A more recent theory, known as lumped damage mechanics, has shown relevant results in obtaining numerical responses considering the nonlinear effects of reinforced concrete structures, based on fundamental concepts of fracture mechanics and damage mechanics, associated with the concept of plastic hinges. The objective of this paper is to continue theoretical studies for the analysis of reinforced concrete frame elements with failure modes due to simultaneous bending and shear forces, proposing a new formulation for the evolution criterion of damage due to shear force. The results indicate that the proposed formulation improves the numerical response of test specimens with predominant failure under shear force.